Korelasi Gaya Belajar dengan Nilai Hasil Belajar Bahasa Arab pada siswa kelas V di SD Khadijah II Surabaya - Rika Azelia Noor Imani; Dewien Nabielah Agustin; Firdausi Nurharini (MUMTAZA Journal of Arabic Teaching, Arabic Linguistic and Literature, 2022)
In learning activities, of course, all teachers want optimal results, but not all learning styles for each student are the same. So that their learning outcomes are also different. The background of this research problem is the difficulty or convenience of students in receiving Arabic lessons with different learning methods. The research question in this study is whether there is a relationship between learning styles and learning outcomes of Arabic for fifth grade students at SD Khadijah II Surabaya. The purpose of this study was to determine the relationship between student learning styles and Arabic language learning outcomes for fifth grade students at SD Khadijah II Surabaya. This research method is quantitative. The population is all students of class V and a sample of 30 students. The data collection method used in this study is a questionnaire and documentation method, as well as statistical data analysis techniques that the authors use to analyze the data collected in this study using the product moment formula. Based on the calculations and data analysis that the researchers did in this study, the results of r count were greater than r table. on the r table at a significance level of 5% so that the hypothesis can be accepted. From the results of the consultation, it can be stated that rxy is 0.6449 greater than rtable at the 5% level of 0.361 which can be formulated as follows 0.6449 > 0.361 which indicates that there is a strong relationship between student learning styles and Arabic learning grades from V SD Khadija II Surabaya.